Factors contributing to inaccurate migraine diagnosis: a prospective study at a tertiary hospital in Southern Thailand - Kanokrat Suwannalaong; Sirianong Sittisomwong; Duangkamon Dutsadeethammo; Prakit Anukoolwittaya; Wanakorn Rattanawong (The Journal of Headache and Pain, 2025)
BACKGROUND: Migraine is a common and disabling neurological disorder, yet diagnostic accuracy remains suboptimal, especially in non-specialist settings. Misdiagnosis may lead to delayed treatment, medication overuse, and reduced quality of life. The objective of this study was to estimate the proportion of patients with migraine attending the headache clinic who were misdiagnosed or not diagnosed as having migraine before attending the headache clinic, and to identify factors associated with inaccurate migraine diagnosis among patients before attending a tertiary hospital in Southern Thailand. METHODS: A prospective, cross-sectional study was conducted at Songkhla Hospital between July 2024 and April 2025. Adult patients (≥ 18 years) with a final migraine diagnosis confirmed by two blinded independent neurologists were enrolled. Participants were divided into two groups: (1) an appropriate diagnosis group, defined as patients who received a correct diagnosis of migraine at their initial consultation with any physicians prior to attending the headache clinic; and (2) an inappropriate diagnosis group, defined as patients who were previously misdiagnosed with another headache disorder or had not been diagnosed with migraine before their headache clinic visit. Data on demographics, clinical features, and the specialty of the first attending physician were analyzed using univariable and multivariable logistic regression. RESULTS: 90 patients were included (87.8% female, mean age 43.4 ± 14.8 years). 43.3% had been misdiagnosed at their initial visit. The most common incorrect diagnoses were tension-type headache and sinusitis. Multivariable analysis identified five independent factors significantly associated with inappropriate diagnosis: male sex (adjusted OR 7.77, 95% CI 1.07-56.50, p = 0.043), bilateral headache (aOR 3.90, 95% CI 1.25-12.13, p = 0.019), lack of worsening by physical activity (aOR 5.09, 95% CI 1.54-16.89, p = 0.008), presence of vertigo/dizziness (aOR 4.39, 95% CI 1.22-15.83, p = 0.024) and initial consultation with a non-neurologist (aOR 7.92, 95% CI 2.63-23.88, p < 0.001),. CONCLUSION: Misdiagnosis of migraine remains frequent in clinical practice, particularly among patients initially evaluated by non-neurologists. Atypical symptom profiles-such as bilateral pain, lack of activity-related exacerbation, or associated vertigo-contribute to diagnostic inaccuracy. Enhanced awareness and targeted education for primary physicians are essential to improve diagnostic precision and reduce treatment delay.
Keywords: Migraine and Headache Studies; Vestibular and auditory disorders; Cerebrovascular and genetic disorders